Genetic basis and timing of a major mating system shift in Capsella. Issue 1 (1st August 2019) - Bachmann, Jörg A.; Tedder, Andrew; Laenen, Benjamin; Fracassetti, Marco; Désamoré, Aurélie; Lafon‐Placette, Clément; Steige, Kim A.; Callot, Caroline; Marande, William; Neuffer, Barbara; Bergès, Hélène; Köhler, Claudia; et al.
Summary: A crucial step in the transition from outcrossing to self‐fertilization is the loss of genetic self‐incompatibility (SI). In the Brassicaceae, SI involves the interaction of female and male specificity components, encoded by the genes SRK and SCR at the self‐incompatibility locus ( S ‐locus). Theory predicts that S‐ linked mutations, and especially dominant mutations in SCR, are likely to contribute to loss of SI. However, few studies have investigated the contribution of dominant mutations to loss of SI in wild plant species. Here, we investigate the genetic basis of loss of SI in the self‐fertilizing crucifer species Capsella orientalis, by combining genetic mapping, long‐read sequencing of complete S‐ haplotypes, gene expression analyses and controlled crosses. We show that loss of SI in C. orientalis occurred < 2.6 Mya and maps as a dominant trait to the S‐ locus. We identify a fixed frameshift deletion in the male specificity gene SCR and confirm loss of male SI specificity. We further identify an S‐ linked small RNA that is predicted to cause dominance of self‐compatibility. Our results agree with predictions on the contribution of dominant S‐ linked mutations to loss of SI, and thus provide new insights into the molecular basis of mating system transitions.